R.I.P to “The feeling” / Noraziah Mohd Amin - Mohd Amin, Noraziah (Academy of Language Studies, 2023)
In the dark, looking for a way out Trying to reach for the door and fumbling about I desperately needed to move out and leave it behind This room of darkness was a prison of the mind Killing my sanity with strangers’ words I long for the soothing songs of chirping birds As I was walking closer to the door With hope to leave the feeling I hate It furiously pulled me back inside Still with anger that didn’t subside It grabbed my neck and tried to pin me down